Variations in hospitalization rates across Parkinson's Foundation Centers of Excellence. (December 2020) - Zeldenrust, Florentine; Lidstone, Sarah; Wu, Samuel; Okun, Michael S.; Cubillos, Fernando; Beck, James; Davis, Thomas; Lyons, Kelly; Nelson, Eugene; Rafferty, Miriam; Schmidt, Peter; Dai, Yunfeng; et al.
Abstract: Introduction: Patients with Parkinson's disease (PD) are at increased risk for hospitalization and often experience worsening of PD when hospitalized. It is therefore important to identify strategies to prevent hospitalization. Methods: Hospital encounter rates in different Parkinson's Foundation Centers of Excellence in United States, Canada, Israel and the Netherlands were analyzed as part of the Parkinson Foundation Parkinson's Outcomes Project (PF-POP). Multivariate logistic regression was used to estimate the odds ratio for hospitalization, adjusted for risk factors. Results: Baseline age, disease duration, other relative than spouse/partner as care giver, cancer, arthritis, other comorbidities, falls, use of levodopa, use of dopamine agonist, use of COMT inhibitor, occupational therapy before the baseline visit, PDQ-39, MSCI total score and time between visits were significantly associated with the risk of hospital encounters. After adjustment for these factors, two centers had significantly lower odds for hospitalization admission and ER visit (minimum OR 0.3) and four centers had significantly higher odds (maximum OR 1.5) than the average center. Four centers had significantly lower hazard ratios for time to re-hospitalization compared to the average center. Reducing hospital admission rates in those centers with higher than average rates would reduce overall hospitalizations by 11%. Applied to PD patients over 65 nationwide this represents a potential for cost savings of greater than $1 billion over 48 months. Conclusion: Encounter rates vary even across expert centers and suggest that practices carried out in some centers may reduce the risk of hospitalization. Further research will be necessary to identify these practices and implement them more widely to improve care for people with PD. Highlights: A major burden for patients with Parkinson's disease is hospital admission. There is significant variation in hospital encounter rates between specialty care centers for Parkinson's disease. This suggests care processes can be modified to reduce hospital encounters. Reducing hospital admission rates to no higher than average represents a major potential cost savings.